2019
DOI: 10.1155/2019/3638926
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Antagonistic Bacteria Paenibacillus jamilae HS-26 and Their Effects on Plant Growth

Abstract: Soilborne pathogens affect plant growth and food production worldwide. The application of chemical fertilizers and pesticides to control plant diseases has harmful effects; fortunately, plant growth-promoting rhizobacteria can be used as a potential alternative strategy. Here, Paenibacillus jamilae HS-26 was selected for its highly antagonistic activity against several soilborne pathogens. The bacterium synthesized hydrolytic enzymes and released extracellular antifungal metabolites and volatile organic compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 52 publications
1
39
0
2
Order By: Relevance
“…Both plants and microbes have access to these soluble Fe 3+siderophore complexes [74]. Previous studies have shown siderophores production in the isolated PGPRs including species of Paenibacillus [75,76]. Raza and Shen et al [59] reported siderophores production in the isolated strain Paenibacillus polymyxa SQR-21 under different iron conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Both plants and microbes have access to these soluble Fe 3+siderophore complexes [74]. Previous studies have shown siderophores production in the isolated PGPRs including species of Paenibacillus [75,76]. Raza and Shen et al [59] reported siderophores production in the isolated strain Paenibacillus polymyxa SQR-21 under different iron conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, PGPR help plant growth by a combination of physiological attributes such as asymbiotic N 2 fixation 15 , phytohormones production namely indole-3-acetic acid (IAA), cytokinin, gibberellins 16 , solubilizing insoluble mineral phosphate, zinc and potassium, etc. 17 , siderophore production 18 and by inhibiting the deleterious fungal phytopathogens 14,19,20 .…”
mentioning
confidence: 99%
“…Cawan petri diinkubasi pada 30C selama seminggu, lalu diamati. Kedua isolat dinyatakan tidak saling menghambat jika tidak ada hambatan pertumbuhan miselium di sekitar koloni Actinomycetes (Khamna et al 2009;Wang et al 2019). Untuk mengetahui sifat antagonisme bahwa antara kedua kelompok isolat bukan merupakan mekanisme persaingan nutrisi maka dilakukan uji blok agar.…”
Section: Uji Antagonisme Antarisolat Terseleksiunclassified